Comparing the governance of large housing estates in Estonia, Germany and Russia. What can be learned? - Bernt, Matthias (My University, 2020)
This report summarizes the findings of the Work Package 2, “Governance Analysis,” of the comparative research project “Estates After Transition.” This 3‑year research project compares six Large Housing Estates in three countries:Russia, Germany, and Estonia. The paper provides initial ideas about the question of how the different governance experiences in the six cases observed can meaningfully be brought into relation to one another. It focuses on the themes of property relations, state capacities, civil society participation,and planning types. The report concludes that the frameworks for these four themes are so different in the three countries that knowledge-transfer can only be successful or useful when it is done in a very context-sensitive way. At the same time, each of the governance formations observed provides both potentials and problems, the analysis of which can support thinking about governance and planning issues in Large Housing Estates “elsewhere.”
Erscheinungsjahr ermittelt.
Keywords: Großwohnsiedlung; Großwohnanlage; Wohnungspolitik; Wohnungsplanung; Eigentumsverhältnis; Wohnungsverwaltung; Ländervergleich